ANALISIS KEABSAHAN PENJATUHAN PIDANA PENJARA DIBAWAH MINIMUM KHUSUS TERHADAP PENGEDAR DALAM TINDAK PIDANA NARKOTIKA( Studi Putusan Pengadilan Negeri Nomor 62/Pid.Sus/2018/PN.Mam) - Nadia Inggrida Hartono (Fakultas Hukum Universitas Tarumanagara, 2021)
Drugsxisxaxcriminalxact that requires extraordinary prevention and handling.One of the efforts drugs is the application of special minimum criminal provisions. Implementation of this special minimum criminal sanction needs to be supported by the judge as the law enforcer who determines the severity of the crimes imposed in the judicial system. Indonesia is a narcotics emergency country, with below-this minimum is considered to lack a sense of justice in the community. The imposition of a prison sentence below this special minimum is considered to hurt the sense of justice of the communit. Basically criminal convictions under a special minimum are the authority of the judge but this needs to be considered to impose a criminal below a special minimum needs to be considered regarding incriminating and mitigating matters.